2016
DOI: 10.1177/1535370216636720
|View full text |Cite
|
Sign up to set email alerts
|

Original Research: Acute chest syndrome in sickle cell disease: Effect of genotype and asthma

Abstract: Sickle cell disease is a severe hemoglobinopathy caused by mutations in the beta globin genes. The disorder has protean manifestations and leads to severe morbidity and early mortality. Acute chest syndrome (ACS) is a common complication and in the USA is the leading cause of death in patients with sickle cell disease. Care of patients with sickle cell disease is complex and typically involves both primary care physicians and hematology subspecialists. The purpose of this study was first to attempt to validate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 18 publications
0
9
0
Order By: Relevance
“…2, 3 This results in significant RBC membrane damage and deformation; and may result in RBC lysis. 4, 5 The complexity of SCD can result in a number of clinical manifestations such as stroke 6, 7 , pulmonary hypertension 8 , cognitive deficiency 9 , and acute chest syndrome 10 which further contributes to increase morbidity and mortality in these patients. Healthy human red blood cells (RBCs) have the ability to change their morphology and structural rigidity in a reversible manner during oxygen transport.…”
Section: Introductionmentioning
confidence: 99%
“…2, 3 This results in significant RBC membrane damage and deformation; and may result in RBC lysis. 4, 5 The complexity of SCD can result in a number of clinical manifestations such as stroke 6, 7 , pulmonary hypertension 8 , cognitive deficiency 9 , and acute chest syndrome 10 which further contributes to increase morbidity and mortality in these patients. Healthy human red blood cells (RBCs) have the ability to change their morphology and structural rigidity in a reversible manner during oxygen transport.…”
Section: Introductionmentioning
confidence: 99%
“…The majority of patients in the SCD-A-P group had the homozygous genotype of SCD type SS, and this group had higher rates of hospital visits for asthma and ACS compared to group SCD-A. Patients with this genotype are known to have more severe disease than patients with the heterozygous genotype (SCD type SC) 1,15 , and they are at higher risk for ACS compared to other SCD genotypes 27 . Thus, patients with SCD type SS should perhaps be referred to the pulmonologist more readily compared to patients with other genotypes.…”
Section: Discussionmentioning
confidence: 94%
“…In our study, the most significant genotypes were HbSS (57%) and Hb SB (43%). Pahl et al [22] evaluated 109 patients and observed that 50% of HbSS and HbSB genotype patients were diagnosed with acute chest syndrome (ACS) at least once during hospitalization due to painful crisis. In our patients, 50.6% were diagnosed with ACS during painful crisis.…”
Section: Discussionmentioning
confidence: 99%